Motivation as a mediator of social disparities in academic achievement - Steinmayr, Ricarda; Dinger, Felix; Spinath, Birgit (European journal of personality, 2012)
The present study aimed at contributing to the understanding of social disparities in relation to students' academic achievement in the science, technology, engineering and mathematics domains. A sample of n = 321 German 11th graders completed measures of their family socio-economic status (SES), general intelligence, domain-specific ability self-concepts and subjective scholastic values in math, physics and chemistry. Students' grades in these subjects received four months after testing served as criteria. Significant mediation effects were found for all motivational variables between fathers' SES and students' achievement, whereas for mothers' SES, only children's academic self-concept in chemistry was a significant mediator. These results also held when students' general intelligence was controlled. Additionally, we controlled for students' grades before testing to investigate which variables mediated the influence of SES on change in school performance. Motivational variables significantly mediated the influence of fathers' SES on change in school performance in math but not in chemistry and physics. Intelligence significantly mediated the influence of fathers' SES on change in school performance in physics and chemistry but not in mathematics. The impact of mothers' SES on change in grades in chemistry was mediated by intelligence. Among others, the reasons potentially accounting for the differential influences of fathers' and mothers' SES are discussed.